MENINGKATKAN HASIL BELAJAR MATA PELAJAR PKN MELALALUI METODE THINK PAIR SHARE PADA KELAS III SD MUHAMMADIYAH 1 LIMBOTO - Karmila Hasan; Thamrin A.Kum; Yurni Rahman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The purpose of this study was to improve Civics learning outcomes through the think pair share method in grade III at Muhammadiyah 1 Limboto Elementary School. The type of research used was classroom action research (CAR) with 28 grade III students as subjects. This study used techniques including interviews, observations, tests, and documentation. Data analysis techniques included teacher activities, student activities, and Civics learning outcomes through the think pair share method. The study was conducted in two cycles: the first cycle with three meetings and the second cycle with two meetings. The four stages were: planning. implementation, observation, and reflection. The results of the study showed that during the initial observation, 6 students, representing 21%, had passed the test, and 22 students, representing 79%, had failed the test. Furthermore, in the first cycle, this number increased to 21 students, representing 75%, with a passing test. In the second cycle, 24 students achieved a passing test, representing 85%. The results achieved in the second cycle exceeded the established performance indicators. Therefore, it can be concluded that the think-pair-share method can improve the leaming outcomes of third-grade students in Civics at Muhammadiyah 1 Limboto Elementary School.